One-Pot Synthesis of Isoquinuclidines via 2,6-Diaryl-1,2-dihydropyridines using (E,E)-Cinnamylideneacetophenones as Templates - Varandas, Pedro A. M. M.; Rocha, Djenisa H. A.; Paz, Filipe A. A.; Silva, Eduarda M. P.; Silva, Artur M. S. (Synthesis, 2018)
Diastereoselective Diels–Alder reactions of 2,6-diaryl-1,2-dihydropyridines with N-methylmaleimide afford highly substituted isoquinuclidines in good chemical yield (30–50%). This sequential one-pot synthesis is performed under microwave irradiation and involves, primarily, the synthesis of 2,6-diaryl-1,2-dihydropyridines by a 6π-azaelectrocyclisation involving an intermediate α,β,γ,δ-di-unsaturated imine, obtained by condensation of (E,E)-cinnamylideneacetophenones with amines. This procedure easily converts unstable 2,6-diaryl-1,2-dihydropyridines into, otherwise inaccessible, isoquinuclidines without any kind of manipulation.
Keywords: nitrogen heterocycles; Schiff bases; electrocyclic reactions; microwave chemistry; Diels–Alder reaction